Measuring Classroom Management in Secondary Settings: Ongoing Validation of the Direct Behavior Rating-Classroom Management. (June 2023) - Sims, Wesley A.; Yu, Rondy; King, Kathleen R.; Zahn, Danielle; Mandracchia, Nina; Monteiro, Elissa; Klaib, Melissa
Classroom management (CM) practices have a well-established, intuitive, and empirical connection with student academic, social, emotional, and behavioral outcomes. CM, defined as educator practices used to create supportive classroom environments, may be the implementation factor that is most impactful of the universal Tier I supports. Recognizing the importance of CM and existing deficiencies in pre- and in-service training for teachers, schools are increasingly turning to data-driven professional development activities as a solution. The current study continues the validation process of the Direct Behavior Rating-Classroom Management (DBR-CM), an efficient and flexible measure of teacher CM practices in secondary school settings. Data were collected from 140 U.S. Midwest middle and high school classrooms. Results found DBR-CM scores to be significantly correlated with several scores on concurrently completed measures of CM, including those that rely on systematic direct observation and rating scales. Findings continue the accumulation of validity evidence to address extrapolation, generalization, and theory-based inferences underlying the interpretation and intended uses of the DBR-CM. Results are promising and build on previous DBR-CM validation work. Limitations and implications are discussed.